Macroeconomics and the Phillips curve myth - Forder, James (Oxford, United Kingdom Oxford University Press, 2014)
This volume reconsiders the role of the Phillips curve in macroeconomic analysis in the first twenty years following the famous work by A.W.H. Phillips, after whom it is named
Includes bibliographical references (pages 253-300) and index.
nmn 24/10/17
Loans
Keywords: Macroeconomics - history - 20th century; Macroeconomics; Phillips curve